Làm sương sương :))
\(P=\frac{\sqrt{x}+1}{\sqrt{x}-2}+\frac{2\sqrt{x}}{\sqrt{x}+2}-\frac{5\sqrt{x}+2}{x-4}\)
\(P=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+2\right)+2\sqrt{x}\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}-\frac{5\sqrt{x}+2}{x-4}\)
\(P=\frac{x+2\sqrt{x}+\sqrt{x}+2+2x-4\sqrt{x}-5\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{3x-6\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}=\frac{3\sqrt{x}\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}=\frac{3\sqrt{x}}{\sqrt{x}+2}\)
Để P = 2 thì \(\frac{3\sqrt{x}}{\sqrt{x}+2}=2\Rightarrow\frac{3\sqrt{x}}{\sqrt{x}+2}-2=0\)
\(\Rightarrow\frac{3\sqrt{x}-2\left(\sqrt{x}+2\right)}{\sqrt{x}+2}=0\Rightarrow\frac{3\sqrt{x}-2\sqrt{x}-4}{\sqrt{x}+2}=0\)
\(\Rightarrow\frac{\sqrt{x}-4}{\sqrt{x}+2}=0\Rightarrow\sqrt{x}-4=0\)
\(\Leftrightarrow x=16\)